Developing School Managers’ Change Management Competency in Competency – Based Training Courses in Vietnam - My Giang Son (European Scientific Journal, ESJ, 2019)
The change management competency is an important competency of school managers in meeting the requirements of school management in the context of the education innovation in Vietnam. This competency can be formed and developed through educating and training of school managers at all levels. This article presents the concept, structure of the change management competency of school managers and development of the change management competency in competency-based training courses in Vietnam. Given the perspective of competency-based training, this article provides recommendations on developing a change management competency in training courses for school managers.